The Queer and the Ominous. Lina Meruane's Poetics of 'Degeneration' - Bizzarri, Gabriele (SOLETRAS, 2019)
Abstract Since the adventures of her Infantas up to the ‘illness involountary trilogy’ (which is where her two major novels Fruta podrida and Sangre en el ojo are framed), Lina Meruane has developped a ‘degenerated’ poetics, charectarized by an insistence on ‘bodies in progress’, i.e. obsessively thematising a metamorfosis which works both as a disturbing element and as a platform for anarchy: an inscrutable source of both fear and pleasure. In fact, the body –which she inflects in a meticulous and hallucinatory inventory of variations, excesses and abjections– operates in her oeuvre like a ‘de-identifying machine’. This essay aims at focusing on the peculiar intersection which seems to explain effectively the unstable living forms that inhabit her texts, one where queer discourse (in all of its rhizomic ramifications) mixes with fantastic and gothic features. If, on the one hand, Meruane’s political agenda clings to the refusal of the disciplinating mould and the objection to any request of identity accountability, on the other, insouciantly flirting with the narrative codes of the ominous, the Chilean writer counterbalances her revolutionary theoric drive, as it is illustrated by the estranging, almost ‘horror’ staging she intends for every one of her ambiguous, amorphous creatures. Resumo Das andanças das suas Infantas à ‘trilogia involuntária da doença’ (da qual formam parte as suas duas novelas maiores: Fruta podrida e Sangre en el ojo), Lina Meruane vem desenvolvendo uma escrita da deslocação e da ‘degeneração’ caracterizada pela tematização obsessiva de uma metamorfose que funciona quer como elemento perturbador, quer como estímulo para a anarquia, causador do medo e do prazer. De facto, nas suas descrições, o corpo –visionária e ambivalentemente observado através de um repertório desconcertante de alterações, excessos e abjeções– funciona como uma autêntica ‘máquina para des-identificar’. Este estudo pretende concentrar-se na intersecção inédita que melhor parece dar conta das formas estranhas e instáveis que habitam cada uma das suas fábulas e, ao mesmo tempo, as definem fora do sistema dos géneros: a que se produz entre o discurso ‘queer’ (com todas as suas ramificações e metáforas: o ‘aberto’, o ‘vulnerável’, o ‘pós-humano’...) e o discurso fantástico (banhado em humores góticos) que também as atravessa. Se, por um lado, a agenda política dos textos de Meruane remete para a recusa da disciplina da forma e para a contestação de tudo o que é identitariamente estabelecido, o jogo constante –aindaque ambíguo– com os códigos narrativos do funesto parece servir à escritora chilena de contrapeso, levando-a a apostar numa encenação alheadora, sinistra, terrorífica até dos resultados revolucionários realizados já desde a teoria. Palavras-chave: Identidade. Deslocação. Lina Meruane. Queer. Fantástico.